About one false „moravism” - Stankov, Rostislav (Studia Ceranea, 2013)
The article deals with a false „moravism” registered in Kievan fragments and in Orationes on Gospel of pope Gregory the Great: инокость ‘peregrinatio’. It is showed off how on a single world, nonexisting cultural traditions could be made.